2008
DOI: 10.1016/j.chom.2008.08.013
|View full text |Cite
|
Sign up to set email alerts
|

HIV Nef Enhances Tat-Mediated Viral Transcription through a hnRNP-K-Nucleated Signaling Complex

Abstract: Although dispensable in vitro, HIV Nef enables high-level viral replication in infected hosts by an as yet unexplained mechanism. Previously, we proposed that Nef functionally cooperates with the viral transactivator Tat by derepressing the viral promoter via a Nef-associated kinase complex (NAKC). Here, we demonstrate that hnRNP-K, a host factor thought to facilitate crosstalk between kinases and gene expression, interacts with Nef and, as part of NAKC, nucleates Nef-interacting kinases, including Lck, PKCdel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 41 publications
(74 reference statements)
4
49
0
Order By: Relevance
“…hnRNP K exists in complexes with ERK1/2 and regulates their activities (40,82). We show that in response to serum treatment, hnRNP K recruitment along the EGR-1 gene is linked to Pol II transcription (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hnRNP K exists in complexes with ERK1/2 and regulates their activities (40,82). We show that in response to serum treatment, hnRNP K recruitment along the EGR-1 gene is linked to Pol II transcription (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP K acts as a docking platform at sites of RNA-directed processes (22,31,82). hnRNP K exists in complexes with ERK1/2 and regulates their activities (40,82).…”
Section: Discussionmentioning
confidence: 99%
“…plex (22). In another study, Hsp40 was shown to interact and co-localize with Nef in the nucleus and thereby augment LTRdriven gene expression (23).…”
mentioning
confidence: 99%
“…The complex between CycK and CDK9 was also shown to function as a CTD kinase in vitro (17). Although Nef was earlier reported as a negative factor for viral replication (32), recent evidence has convincingly demonstrated Nef as an enhancer of viral replication (16,22,(33)(34)(35)(36). Nef performs most of its functions by interacting with cellular proteins.…”
mentioning
confidence: 99%
“…Second, Nef-mediated signaling can enhance Tat-mediated transcriptional activity via an extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK)-dependent pathway (225). Third, Nef promotes Tat-mediated transcription via the heterogeneous nuclear ribonucleoprotein K (hnRNP-K)-nucleated signaling complex (226). Note that hnRNP-K plays essential roles in transcriptional processes and molecular interactions (227).…”
Section: Tat-nef Interactionmentioning
confidence: 99%